Seleksi 16 Galur Harapan Cabai Rawit (Capsicum annuum L.) untuk Toleransi terhadap Salinitas - Musadia Afa; Mustafa, Marlina; Yolanda Fitria Syahri; Juniaty Arruan Bulawan; Musdalifa (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2021)
The utilization of saline soil for chili pepper production might be established by selecting tolerant varieties so that the growth and production remain stable even though they are planted on marginal lands. The purpose of this study was to determine the selection criteria for tolerant chili pepper to salinity and select a chili pepper genotype that are tolerant to salinity based on morphological characters and yield components. This study was carried out in Kolaka Regency, Southeast Sulawesi, from November 2020 to May 2021. The study was carried out on saline land nearby the coast with an average of electrical conductivity (EC) of 6.66 dS m-1. The study used a randomized complete block design with 22 lines of elite chili pepper and three replications. The results showed that characters as selection criteria for salinity tolerant were plant height, days to flowering, days to harvest, and fruit length because they had a significant effect on fruit weight per plant and high broad-sense heritability of 81.53%, 94.75%, 95.05%, and 87.45%, respectively. Based on these characters, the genotype selected as a candidate for the tolerant variety was G17. This genotype can be recommended for the development of chili pepper in saline soil. Keywords: heritability, saline land, tolerance, yield